Potencial antimicrobiano da própolis verde sobre Salmonella enterica subsp. enterica - Maia, Layane Martins (2020)
Over the years, several microorganisms have adapted and bought resistance to drugs. Antimicrobial resistance is considered a global problem for health systems, with no human and animal scope. Salmonella consumes as one of the foodborne pathogens of great impact on public health. The occurrence of episodes with multidrug resistance is real on all continents and alternative methods should be investigated. In this context, the aim of this study was to evaluate the antimicrobial effect of green propolis extracts on Salmonella enterica, as well as to determine the content of bioactive compounds and the sensitivity profile to antimicrobials used in therapeutic use. A propolis was subjected to two types of extraction, ethanolic and ultrasonic, resulting from equal extractions of terminology. Total phenolic compounds, total flavonoid content and total antioxidant activity were quantified by the free radical DPPH. These extracts were diluted in ethanol in the applications: 100; 50; 25; 12.5; 6.25; 3.125; 1.56; 0.8; 0.4; 0.2 and 0.1 mg / mL-1. Two reference strains and 30 species of Salmonella genus processed by agricultural food and environment subsidized by cell viability tests using the microdilution method. Analyze the susceptibility profile of all strains for amikacin (30μg), norfloxacin (10μg), ceftriaxone (30μg), ceftiofur (30μg) and doxycycline (30μg), using the disk-diffusion method. The results showed those that presented a studied and crossed resistance field, and 83.3% (25/30) of the samples were resistant to one or more antimicrobial agents used, only five times without resistance and 21 caused by multiresistants. Cross resistance occurred in 63.3% (19/30) of individuals facing cephalosporins. Regarding the action of ethanol extraction of green propolis, it was identified that the serotypes Agona, Anatum, Cerro, Saintpaul and all as strains of Schwarzengrund are the same or equal responses to minimal inhibition. To serovar, Heidelberg reduced the variability for MIC, using 6.25 to 25 mg / mL-1, as well as for the minimum bactericidal concentration with variations between 50 and 100 mg / mL-1. To extract ultrasound of green propolis from CIM, it presents equal responses for serotypes Agona, Cerro and Saintpaul. For Heidelberg serovar there was a variation for MIC between 6.25 to 25 mg / mL-1, for Schwarzengrund serovar there was a variation between 6.25 to 12.5 mg / mL-1. It is concluded that field isolates reinforce the alert about multidrug-resistant strains for antimicrobial bases chosen for therapeutic use in the context of animal and human health. The extracts of green propolis, due to their concentration of phenolic / flavonoid compounds and their antioxidant components, showed biological antimicrobial action that inhibited, in varying concentrations, Salmonella enterica serotypes from the poultry environment. For these observations, both extracts of green propolis can be considered as a dose-dependent alternative to Salmonella inhibition.